Digital Journalism vs. Traditional Media: Changing the Face of Information Consumption - Rifki Zaitul Ikhlas; Haruto Takahashi; Yui Nakamura (Journal of Humanities Research Sustainability, 2024)
Background. The digital era has changed the way people consume news, with digital journalism increasingly dominating compared to traditional media. Purpose. This study aims to understand the differences in consumption patterns and public trust in the two forms of media, as well as their implications for the quality of the information presented.   Method. The research methods used are a quantitative approach through a survey and a qualitative approach through in-depth interviews with journalists from both types of media. Results. The results of the study show that younger generations are more likely to use digital journalism because of accessibility and speed, while older generations still trust traditional media because of their credibility and validity. Although digital media is used more frequently, the level of trust in the information presented is relatively lower compared to traditional media. This shows that although digital journalism offers quick access, the credibility aspect is still an issue that needs to be improved. Conclusion. The conclusion of the study is that although digital journalism has changed the face of information consumption, the challenges related to the credibility and validity of information remain significant. This research provides important insights into how speed and credibility can be integrated for a more reliable future of journalism.